Fruit and vegetable intake and the risk of stomach and oesophagus adenocarcinoma in the European Prospective Investigation into Cancer and Nutrition (EPIC-EURGAST) - González, C; Pera, G; Agudo, A; Bueno-De-Mesquita, H; Ceroti, M; Boeing, H; Schulz, M; Del Giudice, G; Plebani, M; Carneiro, F; Berrino, F; Sacerdote, C; et al. (2006)
It is considered that fruit and vegetable (FandV) protect against oesophagus and gastric cancer (GC). However, 2 recent meta-analyses suggest that the strength of association on GC seems to be weaker for vegetables than for fruit and weaker in cohort than in case-control studies. No evidence exists from cohort studies about adenocarcinoma of oesophagus (ACO). In 521,457 men and women participating in the EPIC cohort in 10 European countries, information of diet and lifestyle was collected at baseline. After an average of 6.5 years of follow-up, a total of 330 GC and 65 ACO, confirmed and classified by a panel of pathologists, was used for the analysis. We examined the relation between FandV intake and GC and ACO. A calibration study in a sub-sample was used to control diet measurement errors. In a sub-sample of cases and a random sample of controls, antibodies against Helicobacter pylori (Hp) were measured and interactions with FandV were examined in a nested case-control study. We observed no association with total vegetable intake or specific groups of vegetables and GC risk, except for the intestinal type, where a negative association is possible regarding total vegetable (calibrated HR 0.66; 95% CI 0.35-1.22 per 100 g increase) and onion and garlic intake (calibrated HR 0.70; 95% CI 0.38-1.29 per 10 g increase). No evidence of association between fresh fruit intake and GC risk was observed. We found a negative but non significant association between citrus fruit intake and the cardia site (calibrated HR 0.77; 95% CI 0.47-1.22 per 100 g increase) while no association was observed with the non-cardia site. Regarding ACO, we found a non significant negative association for vegetable intake and for citrus intake (calibrated HRs 0.72; 95% CI 0.32-1.64 and 0.77; 95% CI 0.46-1.28 per 100 and 50 g increase, respectively). It seems that Hp infection does not modify the effect of FandV intake. Our study supports a possible protective role of vegetable intake in the intestinal type of GC and the ACO. Citrus fruit consumption may have a role in the protection against cardia GC and ACO. © 2005 Wiley-Liss, Inc.